Corrigendum to “Internal vascular anatomy of the human lacrimal gland: A protocol based on cadaver dissection and three-dimensional micro-computed tomography” [Ann. Anat. 252 (2024) 152207] (Annals of Anatomy (2024) 252, (S0940960223001620), (10.1016/j.aanat.2023.152207)) - Singh, Swati; Chopra, Prakshi; Necker, Fabian; Scholz, Michael; Liphardt, Anna-Maria; Schuster, Louis; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2024)
The authors regret in the article by Singh et al. in volume 252;152207, February 2024, of Annals of Anatomy, the following change should be made in the acknowledgement section: 1. The present work was performed in (partial) fulfillment of the requirements for obtaining the degree of Dr. med (SS).The additional information provided does not influence the conclusions of the study. The authors would like to apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2024-05-31